2D WS2 embedded PVDF nanocomposites for photosensitive piezoelectric nanogenerators with a colossal energy conversion efficiency of ∼25.6%. Issue 37 (16th September 2021) - Bhattacharya, Didhiti; Bayan, Sayan; Mitra, Rajib Kumar; Ray, Samit K.
Abstract : Benefiting from the advantages of low cost, light weight and mechanical flexibility, piezoelectric nanogenerators have the potential for application in renewable energy harvesting from various unexplored sources. Abstract : Benefiting from the advantages of low cost, light weight and mechanical flexibility, piezoelectric nanogenerators have the potential for application in renewable energy harvesting from various unexplored sources. Here, we report the demonstration of the record efficiency of flexible piezoelectric nanogenerators (PENG) using composites of polyvinylidene fluoride (PVDF) and chemically exfoliated tungsten disulfide (WS2 ) nanosheets, which are found to be strongly photosensitive, making them attractive for self-powered optical devices. The presence of two-dimensional (2D) WS2 nanosheets in the PVDF matrix plays a dual role in enhancing the nucleation of the electroactive β-phase as well as inducing strong photosensitivity in the nanocomposite. The PVDF-WS2 composed flexible device is able to produce an enormously high output voltage of ∼116 V (for an impact of 105 kPa) and a piezoelectric energy conversion efficiency of ∼25.6%, which is the highest among the reported values for PVDF-2D material based self-poled piezoelectric nanogenerators. This self-poled piezo-phototronic device exhibits strain-dependent photocurrent at zero bias and exhibits a responsivity of 6.98 × 10 −3 A W −1 at 0.75% strain under the illumination of 410 nm. The fabricated PENG is also able to harvest energy from routine human activities (finger tapping, writing on paper, mouse clicking, etc .) and movement of human body parts. These results open up a new horizon in piezo-phototronic materials through the realization of photosensitive multifunctional PENGs, which can be scaled up for fabricating compact, high performance, portable and self-powered wearable electronic devices for smart sensor applications.